Osteoid Osteoma of the Proximal Femur: Pitfalls in Diagnosis and Performance of Open Surgical Resection - Zeng, Hao; He, Hongbo; Tong, Xiaopeng; Wang, Zhiwei; Luo, Rongsheng; Liu, Qing (Frontiers in Surgery, 2022)
Aims: Proximal femoral osteoid osteoma (OO) is extremely easy to be misdiagnosed or missed. The purpose of this study was to retrospectively analyze the clinical data of patients with proximal femoral OO in order to determine the clinical manifestation and imaging characteristics of the disease, so as to provide help for the preoperative diagnosis and clinical treatment of proximal femoral OO. Methods: This was a retrospective study involving 35 patients with proximal femoral OO admitted into our hospital from January 2015 to January 2021. The baseline characteristics of the participants included; 24 males and 11 females, aged between 13 to 25 (mean 16.2) years old, and the course of the disease was 1 to 14 (mean 6.3) months. We used previous medical experience records of the patients to analyze for the causes of misdiagnosis. Moreover, we compared the difference between preoperative and postoperative treatment practices in alleviating pain in OO patients and restoring hip function. Follow-ups were conducted regularly, and patients advised to avoid strenuous exercises for 3 months. Results: We followed up 35 patients (25 intercortical, 4 sub-periosteal, and 6 medullary) for an average of 41.4 months. We found that 15 patients (42.9%) had been misdiagnosed of synovitis, perthes disease, osteomyelitis, intra-articular infection, joint tuberculosis and hip impingement syndrome, whose average time from symptoms to diagnosis were 6.3 months. Postoperative pain score and joint function score improved significantly compared with preoperative, and complications were rare. Conclusion: Open surgical resection constitutes an effective treatment for proximal femoral OO by accurately and completely removing the nidus. Wrong choice of examination, and the complexity and diversity of clinical manifestations constitute the main reasons for the misdiagnosis of proximal femoral OO.